SOSIALISASI PEMILIHAN PEMINATAN DALAM PROGRAM STUDI EKONOMI ISLAM SEBAGAI UPAYA PENGUATAN KOMPETENSI DAN ARAH KARIER MAHASISWA - Adi Mansah; Siti Jamilah; Hartutik Hartutik; R Melda Maesarach; Jaharuddin Jaharuddin (Taksasila Edukasi Insani, 2025)
The selection of specialization within the Islamic Economics Study Program is a crucial stage in students' academic journey, significantly impacting their competence development and career prospects. However, many students face challenges in choosing a specialization that aligns with their interests and professional aspirations. Therefore, this community engagement initiative aims to provide a structured socialization program introducing the three available specializations: Islamic Economics, Islamic Finance and Banking, and Islamic Business. The socialization was conducted through lectures and interactive discussions, featuring faculty members as key speakers. The results indicate that students require clearer information and more intensive academic guidance in selecting their specialization. This socialization program has helped students understand the curriculum structure, course distribution, and career opportunities associated with each specialization. Based on these findings, it is recommended that periodic socialization sessions be conducted, accompanied by the development of a specialization guide and integration with internship or field study programs to enhance students' understanding of the practical applications of their academic knowledge in professional settings.Keywords: Specialization Socialization, Islamic Economics, Islamic Economics Specialization, Islamic Finance and Banking, Islamic Business, Community Engagement.